Evaluating the function of calcium antagonist on the Cd-induced stress in sperm of Russian sturgeon, Acipenser gueldenstaedtii - Li, Zhi-Hua; Li, Ping; Rodina, Marek; Randak, Tomas (Aquatic toxicology (Amsterdam, Netherlands), 2010)
In the current study, the sperm of Russian sturgeon (Acipenser gueldenstaedtii) was used to evaluate the roles of Verapamil (VRP), a calcium channel blocker, against cadmium (Cd)-induced stress. Sturgeon sperm were exposed for 2h at 50μg/L VRP, 5.0μg/L Cd, the mixture of 50μg/L VRP+5.0μg/L Cd, 50μg/L Cd and the mixture of 50μg/L VRP+50μg/L Cd. After exposure, the sperm motility parameters (motility and velocity), oxidative stress levels (lipid peroxidation [LPO] and carbonyl protein [CP]) and antioxidant enzyme activities (superoxide dismutase [SOD], glutathione reductase [GR], glutathione peroxidase [GPx]) were measured in sturgeon sperm. Compared to the control, Cd-induced stress was apparent as reflected by depressed motility parameters, induced oxidative stress and inhibited antioxidant enzyme activities at both Cd concentrations. In the presence of VRP, Cd-induced stress was reduced in sturgeon sperm, especially all the measured parameters in the sperm exposed at 5.0μg/L Cd returned to control levels, expect for the sperm motility. The present results indicate that VRP can reduce the Cd-induced stress in sturgeon sperm and suggest that using of sperm in vitro assays may provide a novel and efficient means for evaluating the effects of residual metals in the aquatic environment of sturgeon.
Keywords: Animals; Superoxide Dismutase; oxidační stres; glutathionperoxidasa; kadmium; spermie; chemické látky znečišťující vodu; superoxiddismutasa; Water Pollutants, Chemical; Cadmium; Spermatozoa; Oxidative Stress; blokátory kalciových kanálů; Fishes; Glutathione Peroxidase; ryby; peroxidace lipidů; Lipid Peroxidation; verapamil; Male; Verapamil; Calcium Channel Blockers; zvířata; mužské pohlaví; Glutathione Reductase; glutathionreduktasa